Answer:
There is no solution
Step-by-step explanation:
-4(x+3)=16-4x
expand
−4x−12=16−4x
cancel out
−12=16
because −12=16 is false there is no solution.
Hope this helps :)
Answer:
31.11
Step-by-step explanation:
simplify the expression
Answer:
Step-by-step explanation:
7/15
and/or
0.46 reapeted 6
Answer:
x = π - sin^(-1)(3/2) + 2 π n_1 for n_1 element Z
or x = 2 π n_2 + sin^(-1)(3/2) for n_2 element Z
Step-by-step explanation:
Solve for x:
sin(x) = 1.5
1.5 = 3/2:
sin(x) = 3/2
Take the inverse sine of both sides:
Answer: x = π - sin^(-1)(3/2) + 2 π n_1 for n_1 element Z
or x = 2 π n_2 + sin^(-1)(3/2) for n_2 element Z
I’ll try to make a step by step demonstration! Feel free to skip to step 5 for the answer, though
1. The formula for a right triangular prism is (1/2)*base*height*length, and we know what the base (4 cm) and length (8 cm) are, but not the height
2. To find the height we must divide the side triangle into two, which then gives us two right triangles
3. Focusing on just one of the right triangles, its base will be 2 cm rather than 4 (as it has been divided by two) and its hypotenuse will be 4 cm; using Pythagorean’s theorem (a^2 + b^2 = c^2), solve for the missing side (the height), which should end up being √12
4. Multiply! (1/2)4*√12*8 ≈ 55.425
5. Round to the nearest tenth —> 55.4
I hope this helped somewhat! Comment if clarification is needed